Newcastle satisfaction with nursing scales: an instrument for quality assessments of nursing care. Issue 2 (June 1996) - Thomas, L H; McColl, E; Priest, J; Bond, S; Boys, R J
Abstract : OBJECTIVES–To test the validity and reliability of scales for measuring patients' experiences of and satisfaction with nursing care; to test the ability of the scales to detect differences between hospitals and wards; and to investigate whether place of completion, hospital, or home influences response. DESIGN–Sample survey. SETTING–20 wards in five hospitals in the north east of England. PATIENTS–2078 patients in general medical and surgical wards. MAIN MEASURES– Experiences of and satisfaction with nursing care. RESULTS–75% of patients approached to complete the questionnaires did so. Construct validity and internal consistency were both satisfactory. Both the experience and satisfaction scales were found to detect differences between randomly selected wards and hospitals. A sample of patients (102) were sent a further questionnaire to complete at home. 73% returned this; no significant differences were found in either experience or satisfaction scores between questionnaires given in hospital or at home. CONCLUSION–Scales to measure patients' experiences of and satisfaction with nursing in acute care have been developed and found to be valid, reliable, and able to detect differences between hospitals and wards. Questionnaires can be given before patients leave hospital or at home without affecting scores, but those given at home have a lower response rate.